1983
DOI: 10.1088/0031-8949/27/2/006
|View full text |Cite
|
Sign up to set email alerts
|

Energy States and Bloch States for an Accelerated Electron in a Periodic Lattice

Abstract: The Hamiltonian for an accelerated electron in a periodic one-dimensional lattice is written using normalized coordinates. By this means, the exact functional form for the position and energy dependence of the energy eigenstates is obtained without resorting to the usual approximation methods, such as power-series expansions, perturbation procedures or one-band models. Bloch-type wave functions that fully satisfy Schrödinger's time-dependent equation are obtained by superimposing energy eigenstates using the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Early evidence of time‐domain Bloch oscillations (BOs) in superlattices was revealed by transient degenerate four‐wave mixing (DFWM) , yielding results in agreement with the work of Esaki and Tsu . BOs emerge when an electron subject to a perfectly periodic lattice potential executes periodic motion in the presence of an external electric field . In recent decades, BOs were found in various physical systems.…”
Section: Introductionsupporting
confidence: 67%
“…Early evidence of time‐domain Bloch oscillations (BOs) in superlattices was revealed by transient degenerate four‐wave mixing (DFWM) , yielding results in agreement with the work of Esaki and Tsu . BOs emerge when an electron subject to a perfectly periodic lattice potential executes periodic motion in the presence of an external electric field . In recent decades, BOs were found in various physical systems.…”
Section: Introductionsupporting
confidence: 67%
“…known as the Bloch period. There has been a long-standing controversy about the existence of the Wannier-Stark ladder and Bloch oscillations [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and only recently agreement about the nature of the Wannier-Stark ladder was reached. The history of this discussion is carefully summarized in [12,[20][21][22].…”
Section: Wannier-stark Problemmentioning
confidence: 99%
“…In a subsequent paper, 34 they constructed time-dependent Bloch states which were exact solutions of the TDSE by taking linear combinations of the solutions of the TISE with energies corresponding to the WSL. They showed that such solutions of the TDSE remain in a single band and repeat after the period of one Bloch oscillation.…”
Section: Y/(zt) = 1 " (Z) Exp {-Ie"t / R)mentioning
confidence: 99%